Environmental conditions in the mining areas of the Umnugovi province of Mongolia - Gagarinova, Olga; Belozertseva, Irina; Sandag, Enkh-Amgalan; Emelianova, Natalia; Dugarova, Gerelma; Valeeva, Olga; Ganzorig, Ulgiichimeg; Sarantsetseg, Bazarvaani (Mongolian Journal of Geography and Geoecology, 2025)
As part of a collaborative project, soil and well water samples were collected from herder households located near the Oyu Tolgoi and Erdenes Tavan tolgoi deposits in Khanbogd and Tsogttsetsii soums of Umnugovi province to assess contamination levels. In 2024, field investigations included sampling soil and well water from herder households within the mining vicinity. The Oyu Tolgoi company conducts monitoring of water quality and water levels for certain wells of herder households within the mine’s influence zone. However, comprehensive studies on heavy metal contamination in soil and well water among herders in the mining area remain scarce. More than 20 groundwater samples and over 30 soil samples were collected from areas adjacent to the coal mining operations at the Erdenes Tavan Tolgoi deposit and the copper mining facility at the Oyu Tolgoi deposit. Chemical and analytical procedures were conducted under both field and laboratory conditions using standard methodologies. Metal concentrations were determined by atomic emission spectrometry. Petroleum hydrocarbon contents were measured using a Fluorat analyzer. Soil pH (pH_H2O) was determined potentiometrically. Organic carbon content (Corg) was measured using the wet oxidation method according to Tyurin. High concentrations of nickel, copper, zinc, and arsenic, exceeding sanitary and hygienic standards by several fold, were detected in soils of adjacent territories. Near coal mining enterprises, the total soil pollution index (∑c) corresponds to the “moderately dangerous” and “dangerous” pollution categories. Elevated levels of sodium, fluoride, magnesium, chloride, sulphates, and several heavy metals have been detected in groundwater used for residents’ water supply. In the vicinity of copper and coal mining enterprises, the water pollution index (WPI) is elevated. Monitoring of water resources conducted by mining enterprises in production areas also indicates contamination and depletion of groundwater. However, these enterprises do not conduct ecological assessments of other natural environmental components.